Особливості представлення інформації на паперових носіях - Космацька, Наталя Валеріївна; Kosmatska, N. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Статтю присвячено мовним особливостям писемних повідомлень на паперових носіях. Досліджено організацію повідомлення у формальному та змістовому аспектах, аналізуються графічні засоби оформлення тексту. Зроблено короткий екскурс в історію розвитку поштової кореспонденції. На основі наведених прикладів визначено, що головні ознаки письмових повідомлень – чітка структура, стандартні вирази й конструкції, стилістично нейтральна лексика. The article deals with writing texts meant for the transmission of formal and personal messages. The language peculiarities of the communication on the paper medium are analyzed as well as their internal and external structure organization and graphic means of text presentation. The French letters, postcards and telegrams created in different periods of the development of post services are examined, the history of post messaging is outlined. Cited instances reveal that well-defined structure, standardized expressions and constructions, simple sentences, passive voice, stylistically neutral words characterize formal messages. The personal orientated information resorts to the detailed sentences, stylistically nuanced words whose register fluctuates from casual to frozen, unwonted disposition on the page as well as lines’ length.
Peculiarities of the Presentation of the Information on Paper Medium
Keywords: повідомлення; message; лист; letter; листівка; postcard